Building a Translengua in Latina Lesbian Organizing. Issue 3 (3rd July 2017) - Torres, Lourdes
ABSTRACT: This article discusses the challenges and rewards, as well as the affective labor, involved in forging a Latina lesbian "translengua, " in other words a common language in the context of Latina lesbian organizing. I explore how members of Latina Lesbians en Nuestro Ambiente (LLENA) and Amigas Latinas, Chicago-based Latina lesbian organizations, attempted to foster consensus for collective action in the face of language differences and preferences. Through analysis of archives and interviews with activists, I untangle how LLENA and Amigas Latinas negotiated deeply personal and sensitive issues around language use as they worked to build an inclusive movement. I also identify strategies used to enact a translengua that could bridge linguistic differences within the Latina lesbian community.